Hydrogeological regime and groundwater occurence in the Anthemountas River Basin - Kazakis, N.; Voudouris, K.; Vargemezis, G.; Pavlou, A. (Bulletin of the Geological Society of Greece, 2013)
The Anthemountas river basin is located in northern Greece and covers an area of 374 km2. The mountainous part of the basin consists of ophiolitic, crystalline and carbonate rocks, whereas the lowlands comprise Neogene and Quaternary sediments. Porous aquifers are developed in neogene and quaternary deposits of confined and/or unconfined conditions. Karstic aquifers are developed in the carbonate rocks and there are aquifers in the Mesozoic and Palaeozoic fissured rocks. The water demands of the basin are mainly met by the exploitation of the porous aquifers through a large number of boreholes (more than 1000). The aquifers of fissured rocks discharge through cold springs without significant flow rate. Thermal hot springs are recorded across the Anthemountas fault discharging a mixture of geothermal fluids and cold water from the karst aquifer. According to their hydrogeological and lithological characteristics, porous aquifers can be divided into the subsystems of Galatista and Galarinos in the eastern part of the Anthemountas basin, Vasilika-Risio-Thermi and Tagardes-Trilofos in the western part and Peraia-Agia Triada and AUTh farm-Makedonia airport in the coastal area. For the determination of the aquifers (geometry and anatomy), their recharge mechanisms and hydraulic connection, data from geological maps, lithological profiles, geoelectrical soundings and tomographies, pumping tests and groundwater level measurements are used.